O nowy kształt edukacji literackiej w szkole średniej (dyskusje i polemiki w latach 1870-1918) = For the new form of literal education in secondary school (discussion and polemica in 1870-1918) - Kulka, Bronisława (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The years 1870-1918 on the teritorries anexed by Prussia and Russia after partition of Poland meaned a very difficult situation of learning Polish becouse in this time the occupants'goverments increased the denationalization actions against Poles. Only Galicia had some autonomy sa Polish was learnt at schools and futhermore Polish was officialy used there as an explanation language. The characteristic marks of the situation there were the increased dissatisfaction and crtitics of school programmes what in consequence realized the necessit of reforms. It was the subject of press articles, of meetings and the polenary meetings of teachers' groups.
Keywords: dydaktyka literatury; szkolnictwo ponadpodstawowe; Polska; 19-20 w.